2012
DOI: 10.1093/ndt/gfr811
|View full text |Cite
|
Sign up to set email alerts
|

Arteriolar vascular smooth muscle cell differentiation in benign nephrosclerosis

Abstract: This is the first systematic analysis of VSMC differentiation in bN. The results suggest that smoothelin is the most sensitive marker for the contractile phenotype and that S100A4 could be a novel marker for the secretory phenotype in vivo. The other markers did not seem to differentiate these phenotypes in bN. Thus, VSMC phenotype markers should be defined in the context of the vessel segment and disease under examination. S100A4 could not only be a marker of pro-fibrotic secretory VSMCs in bN but also an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…FSP1 has also been used as an early marker for epithelial-mesenchymal transition and may play important roles during fibrosis39404142. Arteriole SMCs were found to express FSP1 in benign nephrosclerosis samples and thought to contribute to fibrosis process43. In contrast to the traditional opinion that FSP1 expression is indicative of fibrosis, our results showed that FSP1 + cells still retain the capability of forming microvessels.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…FSP1 has also been used as an early marker for epithelial-mesenchymal transition and may play important roles during fibrosis39404142. Arteriole SMCs were found to express FSP1 in benign nephrosclerosis samples and thought to contribute to fibrosis process43. In contrast to the traditional opinion that FSP1 expression is indicative of fibrosis, our results showed that FSP1 + cells still retain the capability of forming microvessels.…”
Section: Discussioncontrasting
confidence: 75%
“…However, there is evidence that the cells involved in these two processes may be related. For example, pericytes or perivascular progenitor cells171819 and SMCs43 have been reported to give rise to myofibroblasts during fibrosis. On the other hand, there has also speculation that myofibroblasts, when put in the right microenvironment, such as the media layer of large blood vessel walls, might differentiate into SMCs35, suggesting the possibility of reciprocal transformation of the two processes.…”
Section: Discussionmentioning
confidence: 99%
“…Cx43, which has been reported in fibroblasts (Zhang et al, 2008) and pericytes (Mogensen et al, 2011), was found in the pool of Nestin-GFP- cells, representing 10 ± 2.0 % of all cells in culture. The α-SMA marker, which has been found in vascular smooth muscle cells (Bockmeyer et al, 2012) and pericytes (Mogensen et al, 2011), is also present in Nestin-GFP-cells, accounting for 29 ± 5.8 % of all cells (Figs. 1A, B).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of hyalinosis, the subendothelial presence of accumulated plasma proteins likely triggers the SMC response of dedifferentiation and synthesis of ECM proteins. 54,55 This concept is schematically depicted in Figure 9.…”
Section: Discussionmentioning
confidence: 99%